Risk Disclosure and Risk Appetite in the UK Retail Sector - Jacklis, Ola (2012)
ABSTRACT In this phase of globalization, companies are constantly faced with the potential for risk which can compromise their current position. Being susceptible to risk can affect not only companies’ business operations but also the decision making process that evidently determines how they are managed. As a consequent, managing and reporting of risk have increasingly attracted interest from various participants throughout the business field. This research is centred on the UK retail sector by conducting a thematic content analysis on eight annual reports of major UK retailers. It is comprised of two parts: The first section is a literature review of the topic of risk disclosure including a discussion of its importance, theories behind its application and its methods. The review also investigates the rise and importance of determining a company’s risk appetite. The first part also provides a review of the UK retail sector and covers the major issues related to the business of retailing including retailers’ position of the risk management process. The second part of this study covers the methodology and method of analysis. It also introduces the major findings and results that were obtained upon completion of the analysis stage. This section ends with the research conclusion which outlines the major conclusions, contributions, recommendations and limitations.